2014
DOI: 10.1021/jm500849z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Millepachine Derivatives As a New Class of Tubulin Polymerization Inhibitors

Abstract: Twenty-one novel derivatives of millepachine were synthesized and evaluated for their in vitro antiproliferative activity. Among them, 8 exhibited the most potent activity, with IC50 values of 8-27 nM against panel of cancer cell lines and retained full activity in multidrug resistant cancer cells. Treated cells were arrested in G2/M phase and resulted in cellular apoptosis. Microtubule dynamics confirmed 8 was a novel tubulin polymerization inhibitor by binding at the colchicine site. 8 also exhibited antivas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…Several studies using microtubule dynamics and competitive assays have provided support that this compound inhibits tubulin polymerization by binding at the colchicine site. 293295 In addition to simple chalcones, chalcones with fused structures ( 71 – 73 , 76 ) have also exhibited antimicrotubule and cytotoxicity effects. Bu et al synthesized a novel o -aryl chalcone ( 74 ) by the Suzuki–Claisen–Schmidt reaction.…”
Section: Medicinal Aspects Of Chalconesmentioning
confidence: 99%
“…Several studies using microtubule dynamics and competitive assays have provided support that this compound inhibits tubulin polymerization by binding at the colchicine site. 293295 In addition to simple chalcones, chalcones with fused structures ( 71 – 73 , 76 ) have also exhibited antimicrotubule and cytotoxicity effects. Bu et al synthesized a novel o -aryl chalcone ( 74 ) by the Suzuki–Claisen–Schmidt reaction.…”
Section: Medicinal Aspects Of Chalconesmentioning
confidence: 99%
“…1) showed the most promising antitumor activity in four xenografts models including resistance tumor-cell bearing mice models [2,3]. Meanwhile, microtubule dynamics also confirmed that SKLB-M8 was a novel tubulin de-polymerization agent by binding at the colchicine site and exhibited excellent anti-vascular activity [3]. To comprehensively evaluate the mechanisms of its antitumor activity, further metabolic research on SKLB-M8 was necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Among these analogs, (E)-3-(3-amino-4-methoxyphenyl)-1-(5-methoxy-2,2-dimethyl-2H-chromen-8-yl)prop-2-en-1-one hydrochloride (SKLB-M8) (Fig. 1) showed the most promising antitumor activity in four xenografts models including resistance tumor-cell bearing mice models [2,3]. Meanwhile, microtubule dynamics also confirmed that SKLB-M8 was a novel tubulin de-polymerization agent by binding at the colchicine site and exhibited excellent anti-vascular activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…14 Some chalcon derivatives also exhibited potent activity as microtubule polymerization inhibitor. 17 Indanones and their derivatives are important bioactive molecules that have been studied to determine their biological activities for the treatment of disease including Alzheimer' s disease 18 and cancer. 15 Bu reported the synthesis and evaluation of a series of cytotoxic ortho-aryl chalcones as new scaffold targeting tubulin and mitosis.…”
Section: Introductionmentioning
confidence: 99%